Potential of sense of place in cultural heritage conservation: a systematic review - Ma, Yue; Mohd Ariffin, Noor Fazamimah; Abdul Aziz, Faziawati; He, Xiao; Liu, Yuanyuan; Feng, Shuning (Universiti Putra Malaysia Press, 2023)
Sense of place is a fundamental aspect of cultural heritage conservation and management, as it plays an important role in understanding the connection between individuals and the places they inhabit. This study aims to provide heritage managers and scholars with up-to-date insights into the importance of a sense of place in maintaining cultural heritage. The main objectives of this research are to explore whether a sense of place’s role in cultural heritage research has been adequately investigated and to assess the sense of place potential in cultural heritage conservation. We conducted a systematic literature review of 42 articles to achieve these goals. Through thematic analysis, this study reveals a sense of place’s impact on various aspects of cultural heritage conservation. From the results, six prominent themes emerged, highlighting that a sense of place is a key determinant in the effectiveness of cultural heritage management initiatives. Based on these findings, authors advocate for enhanced collaboration between the government and local communities, acknowledging the importance of heritage tourism and reinforcing policies for cultural heritage conservation to bolster the sense of place. In future research, examining a sense of place can expand to interdisciplinary intersections, quantitative studies, cross-national comparative research, and the exploration of the role of technology in augmenting both the sense of place and cultural heritage conservation.